2020
DOI: 10.1186/s43055-020-00376-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of chest computerized tomography and oxygen saturation for patients with COVID-19

Abstract: Background COVID-19 is a pandemic disease and is important to know the nature of the disease during follow-up. We aimed to study different imaging signs and changes that occurred during the initial scan, follow-up, and complications. Moreover, to study the CT severity score and its relation to the patients’ clinical condition using oxygen saturation as a parameter. This was a retrospective study conducted on 125 patients, including 293 CT studies, from March till the end of August 2020. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Another study also confirmed that severe/critical patients with respiratory rate ≥ 30 times/min and SpO2 of 93% or less in a resting state had higher total CT scores than ordinary COVID-19 patients [ 23 ]. Aalinezhad [ 24 ] and Osman[ 25 ] et al also reported higher chest CT score is inversely associated with O2 saturation. Furthermore, a multicenter cohort study demonstrated that consolidation in upper lungs on the initial chest CT of COVID-19 patients was associated with increased odds of adverse endpoints, including SpO2 < 93% and partial arterial pressure of oxygen less than 60 mm Hg on room air [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also confirmed that severe/critical patients with respiratory rate ≥ 30 times/min and SpO2 of 93% or less in a resting state had higher total CT scores than ordinary COVID-19 patients [ 23 ]. Aalinezhad [ 24 ] and Osman[ 25 ] et al also reported higher chest CT score is inversely associated with O2 saturation. Furthermore, a multicenter cohort study demonstrated that consolidation in upper lungs on the initial chest CT of COVID-19 patients was associated with increased odds of adverse endpoints, including SpO2 < 93% and partial arterial pressure of oxygen less than 60 mm Hg on room air [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Osman, et al and Annunziata, et al have documented changes in SpO 2 in non-ivermectin treated COVID-10 patients [24,25]. These two studies show unequivocally that there is an initial dip in SpO 2 towards day 8 before a recovery towards day 14.…”
Section: Discussionmentioning
confidence: 95%
“…This coincided with the higher rates of pulmonary and extra-pulmonary comorbidities or complications in addition to the increased prevalence of five CT findings of severity, including the “crazy-paving” pattern, “air-bubble” sign, significant mediastinal nodal enlargement, pericardial effusion, and spontaneous pneumo-mediastinum. Previous studies described the “crazy-paving” pattern in 100% of their severe patients, including Ali TF et al [ 22 ], Ghweil AA et al [ 26 ], Metwally M.I et al [ 27 ], and Osman AM et al [ 28 ]. Additionally, Li Y et al [ 29 ] correlated the presence of pericardial effusion to the high clinical severity.…”
Section: Discussionmentioning
confidence: 99%